Evaluasi Kesesuaian RTH terhadap RTRW Kota Pariaman - Pahlevi, Arbiansyah Reza; Syarief, Azhari (Lembaga Yasin AlSys, 2024)
This research is related to assessing the reasonableness of the area of green open space (RTH) towards the development strategy of Pariaman City as stated in the Regional Regulation (Perda) of the Regional Spatial Planning (RTRW) of Pariaman City for 2010-2030, namely 30% and aims to, 1) Find out distribution and extent of availability of green open space (RTH) in Pariaman City. 2) Knowing the suitability between green open space (RTH) and Regional Spatial Planning (RTRW). This research is a quantitative exploration using spatial methodology. Using Sentinel-2 satellite imagery and the Normalized Difference Vegetation Index (NDVI) identification method, the analysis used focuses on the distribution of green vegetation throughout Pariaman City. The vegetation distribution obtained was overlaid with shapefile data (SHP) obtained from the digitization of the Regional Regulations (Perda) of the Regional Spatial Planning (RTRW) of Pariaman City for 2010-2030, so that the area, distribution and suitability are known. The results of identifying 3946.09 Ha of green open space (RTH) from 4118.76 Ha which were planned in detail, namely; City Park RTH, planned area 3214.16 Ha and area in the field 3087.12 Ha, City Forest RTH, planned area 174.8 Ha and area in the field 174.23 Ha, Cemetery Open Space, planned area 4.72 Ha and area in field 4.67 Ha, RTH Road Route, planned area 504.14 Ha and area in the field 472.53 Ha and RTH Tourism Area, planned area 220.94 Ha and area in the field 207.54 Ha. The percentage of Pariaman City's green open space to the area is 59.57% and has fulfilled the provisions of the RTRW Regional Regulation, namely a minimum green open space of 30%.